Propagation of papaya (Carica papaya L.) cv. Shahi through in vitro culture (Bangladesh Journal of Botany, 2013)
A large number of shoots regenerated from lateral buds and young leaves of Carica papaya L. cv. Shahi on MS supplemented with 1.0 mg/l zeatin and 0.2 mg/l NAA. Addition of 200 mg/l casein hydrolysate (CH) to the medium increased the number of shoots per culture and incorporation of 2.0 g/l activated charcoal (AC) to the medium resulted effective shoot growth with healthy leaf. While addition of 100 mg/l urea and 2.0 g/l activated charcoal to the medium showed proper shoot elongation. Best rooting was obtained from shoots cultured on half-strength of MS fortified with 4.0 mg/l IBA.Within four weeks of transfer to the rooting medium, 90% microcuttings produced 12 - 14 roots. The regenerated plantlets were successfully transferred to potted soil. About 84% plantlets survived in the experimental field. DOI: http://dx.doi.org/10.3329/bjb.v41i2.13448 Bangladesh J. Bot. 41(2): 191-195, 2012 (December)